Pharmaceutical spending in non-specialized hospitals with pediatric patient admission. - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
The management of pharmaceutical resources in healthcare settings is an essential component of hospital administration, impacting both economic sustainability and the quality of care. Among various types of hospitals, non-specialized hospitals, especially those handling pe- diatric admissions, face unique challenges in controlling pharmaceutical costs while ensuring effective treatment. In these settings, pharmaceutical spending is influenced by several factors, including the volume of pediatric cases, the complexity of treatments required, and the availability of specialized medications.